2015
DOI: 10.1128/mbio.00868-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Evolution and Innovation across the Four Major Lineages of Cryptococcus gattii

Abstract: Cryptococcus gattii is a fungal pathogen of humans, causing pulmonary infections in otherwise healthy hosts. To characterize genomic variation among the four major lineages of C. gattii (VGI, -II, -III, and -IV), we generated, annotated, and compared 16 de novo genome assemblies, including the first for the rarely isolated lineages VGIII and VGIV. By identifying syntenic regions across assemblies, we found 15 structural rearrangements, which were almost exclusive to the VGI-III-IV lineages. Using synteny to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
147
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(157 citation statements)
references
References 77 publications
9
147
0
1
Order By: Relevance
“…phagocytosis, IPR, vomocytosis, cryptococcal mitochondrial tubularization and macrophage death) in replicate (3X–8X) over a timecourse of macrophage interaction (0, 18, 24 and 48 h). First, we measured the maximal intracellular proliferate potential ( T max ; commonly referred to as IPR) for 20 isolates of C. gattii including four of the six named subclades (the outbreak clades VGIIa and VGIIc, the recently described VGIIx [24], and VGIIb; figure 1 and electronic supplementary material, table S2). These strains were selected, according to previous literature and strain detail knowledge, to represent a balanced collection of strains (i) from the North Pacific C. gattii outbreak, (ii) from environmental origin, and (iii) representing the different molecular groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…phagocytosis, IPR, vomocytosis, cryptococcal mitochondrial tubularization and macrophage death) in replicate (3X–8X) over a timecourse of macrophage interaction (0, 18, 24 and 48 h). First, we measured the maximal intracellular proliferate potential ( T max ; commonly referred to as IPR) for 20 isolates of C. gattii including four of the six named subclades (the outbreak clades VGIIa and VGIIc, the recently described VGIIx [24], and VGIIb; figure 1 and electronic supplementary material, table S2). These strains were selected, according to previous literature and strain detail knowledge, to represent a balanced collection of strains (i) from the North Pacific C. gattii outbreak, (ii) from environmental origin, and (iii) representing the different molecular groups.…”
Section: Resultsmentioning
confidence: 99%
“…The first gene (CNBG_1370) is a 1 : 1 orthologue of C. neoformans H99 Utr2 gene (with homology to chitin transglycolase), which is potentially involved in capsule biosynthesis [35]. In C. gattii, this gene is under selection in the recently named VGIIx subclade [24] with d N = 0.0063, d S = 0.0059, ω = 1.0792. The second gene (CNBG_0047) is in an orthogroup with C. neoformans H99 Cap64-like proteins Cas31 and Cas3, and under selection in VGIIb ( d N = 0.0028, d S = 0.0023, ω = 1.2242).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pertinent example is expounded by Farrer [13], where comparative genomics were used to analyse lineages of the basidiomycete fungus Cryptococcus gattii that are emerging as a cause of fatal human meningitis across the Pacific Northwest of the USA and Canada. These, and accompanying analyses [14], have shown that four major genetic lineages of C. gattii occur exhibiting extensive genome diversification that is associated with variation in virulence. Broad-scale interlineage processes, such as gene expansion/contraction and mitochondrial recombination, through to fine-scale intralineage microevolutionary events, such as positive selection of single-nucleotide polymorphisms, were shown to be associated with variation in virulence across this species.…”
Section: (I) Biological Drivers Of Emerging Fungal Infectionsmentioning
confidence: 99%
“…Orthologs to genes of known function in C. neoformans H99 were identified in C. 676 gattii R265 using OrthoMCL (48) across 16 isolates as previously described (7). 677…”
mentioning
confidence: 99%